Physics of tearing mode rotation and slow-down in the RFX-mod tokamak. (1st December 2022) - Cordaro, L.; Zanca, P.; Zuin, M.; Auriemma, F.; Fassina, A.; Martines, E.; Zaniol, B.; Cavazzana, R.; De Masi, G.; Grenfell, G.; Momo, B.; Spagnolo, S.; et al.
Abstract: We present a study of the fast, spontaneous rotation regime of tearing modes (TM) in the RFX-mod circular tokamak discharges. Integrated analyses of magnetic, flow and kinetic measurements, are discussed. This analysis of rotation frequency components related to the ion flow and diamagnetic drift shows that the TM fast rotation is mainly driven by the diamagnetic drift. The global decrease of the temperature profile, induced by a growing mode amplitude, can explain the slowing-down of the rotation, which in turn can trigger a potentially disruptive sequence. We show that in RFX-mod the slowing-down cannot be explained solely on the basis of the electromagnetic torque with the external conductive structures, as often reported in literature from other experiments. This analysis, indeed, suggests a strong relationship between the TM dynamics and the transport physics. Statistical analysis of disruptions with slowing down of island rotation shows that TMs take a part in the disruption, even without a locking to the wall.